2006
DOI: 10.1161/01.atv.0000216119.79008.ac
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cyclooxygenase-2 Inhibition With Celecoxib Decreases Angiotensin II-Induced Abdominal Aortic Aneurysm Formation in Mice

Abstract: Objective-Inflammation plays an integral role in the development of abdominal aortic aneurysms (AAAs), and the expression of cyclooxygenase (COX)-2 is increased in aneurysmal tissue compared with normal aorta. Nonsteroidal anti-inflammatory drugs, which inhibit the activity of COX-1 and COX-2, decrease AAA expansion in humans and animal models of the disease. In the current study, we investigated the effectiveness of selective inhibition of COX-1 or COX-2 in attenuating AAA formation. Methods and Results-Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 50 publications
8
112
0
2
Order By: Relevance
“…20 Furthermore, NSAID use is associated with a reduction in abdominal aortic aneurysm expansion. 16,17 In the current issue of Arteriosclerosis, Thrombosis, and Vascular Biology, King et al 21 investigate the roles of COX-1 and COX-2 in a model of abdominal aortic aneurysm. Abdominal aortic aneurysms are caused by local permanent dilation, leading to tissue remodelling, weakening, and the potential of rupture.…”
Section: See Page 1137mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, NSAID use is associated with a reduction in abdominal aortic aneurysm expansion. 16,17 In the current issue of Arteriosclerosis, Thrombosis, and Vascular Biology, King et al 21 investigate the roles of COX-1 and COX-2 in a model of abdominal aortic aneurysm. Abdominal aortic aneurysms are caused by local permanent dilation, leading to tissue remodelling, weakening, and the potential of rupture.…”
Section: See Page 1137mentioning
confidence: 99%
“…In man, abdominal aortic aneurysms demonstrate pronounced local inflammation and contain high levels of COX-2, PGE 2 , and proteolytic enzymes. Using a murine model of angiotensin II-induced abdominal aortic aneurysm, King et al 21 show that selective inhibition of COX-2 with oral dosing of celecoxib dramatically reduced the incidence (control, 74%; celecoxib-treated, 11%) and severity of abdominal aortic aneurysms in apoE Ϫ/Ϫ knockout mice. Inhibition of COX-1 using the COX-1-selective inhibitor SC560 was without effect.…”
Section: See Page 1137mentioning
confidence: 99%
“…Some evidence has suggested that CCL5 also has an important role in Ang II induced dissecting AAA [41]. Moreover, Ang II may stimulate the expression of cyclooxygenase-2 (COX-2) [42,43], a critical enzyme in AAA pathogenesis that forms vasoactive and inflammatory prostaglandins. Indeed, it has been shown that COX-2 deficiency attenuates Ang II infusion-mediated dissecting AAA [44].…”
Section: Renin Angiotensin System -Classical Systemmentioning
confidence: 99%
“…King at al. 61 studied nonsteroidal anti-inflammatory drugs (NSAID), which inhibit the activity of COX-1 and COX-2, to evaluate the effect in an angII-induced AAA mouse model. They noted celecoxib decreased the incidence and severity of AAA formation in both hyperlipidemic and nonhyperlipidemic mice.…”
Section: Pharmacotherapymentioning
confidence: 99%